2015
DOI: 10.1038/srep10431
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the dynamic life story of a Bronze Age Female

Abstract: Ancient human mobility at the individual level is conventionally studied by the diverse application of suitable techniques (e.g. aDNA, radiogenic strontium isotopes, as well as oxygen and lead isotopes) to either hard and/or soft tissues. However, the limited preservation of coexisting hard and soft human tissues hampers the possibilities of investigating high-resolution diachronic mobility periods in the life of a single individual. Here, we present the results of a multidisciplinary study of an exceptionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
122
2
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(140 citation statements)
references
References 30 publications
(51 reference statements)
2
122
2
14
Order By: Relevance
“…These findings contrast with the recently published findings of another comparable (in relation to status, age and prehistoric Period) nonlocal Bronze Age female individual unearthed in Denmark, the “Egtved Woman”, which showed a very different mobility pattern of repeated travels during at least the last two years of her life [5]. Furthermore, the strontium isotope analyses of the Egtved Woman’s scalp hair, nail and tooth enamel were interpreted such that this individual spent less than a year, cumulatively, in present-day territorial Denmark over her life span.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…These findings contrast with the recently published findings of another comparable (in relation to status, age and prehistoric Period) nonlocal Bronze Age female individual unearthed in Denmark, the “Egtved Woman”, which showed a very different mobility pattern of repeated travels during at least the last two years of her life [5]. Furthermore, the strontium isotope analyses of the Egtved Woman’s scalp hair, nail and tooth enamel were interpreted such that this individual spent less than a year, cumulatively, in present-day territorial Denmark over her life span.…”
Section: Resultscontrasting
confidence: 97%
“…This type of detailed mobility investigations of single individuals is possible when hair and/or nails are also preserved [5,9]. Similarly, age determination can be more precise when several techniques are combined.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Font and colleagues found endogenous Sr to be the most significant contributor to the geospatial signal encoded in the 87 Sr/ 86 Sr of hair, while several other studies conversely found strong relationships between exogenous sources and the 87 Sr/ 86 Sr of hair . Therefore, separating the factors contributing to the 87 Sr/ 86 Sr of hair is paramount for utilizing this analytical tool in anthropologic studies …”
Section: Resultssupporting
confidence: 89%
“…Reconstructing the provenance of an individual is important to many anthropologic and forensic investigations . Stable isotope ratios recorded in human scalp hair have utility in reconstruction of the movement histories of individuals . This is because hair keratin and its isotopic signatures are recorders of an individual's environment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation